Towards a better integration of the informal sector : three empirical essays on the interaction between formal and informal firms in Egypt and beyond - (:unkn) unknown (My University, 2017)
Despite the impressive economic growth of African economies since 2000s, the actual context is threatening the sustainable development of the private sector. Large institutional imperfections and poor business environment are hindering the development of firms and are paving the way for a more persistent informal sector. This thesis reopens the controversial debate about the informal sector by looking at its entrepreneurial capacity rather than its threats. In order to understand the strong persistence of this sector despite its confirmed negative impacts, we investigate the extent to which the relationship between formal and informal firms, through market competition, could affect the Egyptian economy. We find that more intense competition stemming from informal firms can drive formal firms to become more productive. We also extend our analysis to Sub-Saharan African countries by underlining the effect of taxation and regulation on the strength of competition between formal and informal firms. Our findings call on the importance of introducing the informal sector in undertaken policies that target the reform of taxation and regulations in Africa. These policies should also target the firms’ access to source of finance, infrastructure and training as effective tools inducing the formalization process and fostering economic growth. Therefore, this thesis provides evidence on the importance of revisiting the impacts of the informal sector in developing countries by looking at it as a driver of economic growth rather than a threat.
Keywords: African Research